A rare case report of fungal esophagitis combined with giant gastric ulcer in an immunocompetent patient. Issue 3 (January 2019) - Liang, Ma; Liwen, Zhang; Juan, Dai; Yun, Zhuang; Yanbo, Ding; Jianping, Chen
Abstract: Rationale: Fungal infection of gastrointestinal (GI) tract is usually seen in immunocompromised patients, but can rarely occur in immunocompetent people in whom no permissive factor is present. Patient concerns: We describe a 68-year-old male immunocompetent patient presenting with simultaneous fungal esophagitis and giant gastric ulcer. Diagnoses: Repeated endoscopic biopsies were taken from the giant gastric ulcer edge and base and histology demonstrated granulation tissue and pseudohyphal fungal forms. Interventions: The patient was treated with fluconazole and omeprazole for 8 weeks. Outcomes: After antifungal treatment with fluconazole, the patient's clinical symptoms gradually disappeared with the healing of gastric ulcer, which never recurred in this patient until 3 months after follow-up. Lessons: Nonhealing gastroesophageal ulcers highlights the importance of repeated endoscopies and biopsies.